2016
DOI: 10.1002/ehf2.12090
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of asymptomatic left ventricular diastolic dysfunction and its association with self‐rated health and N‐terminal B‐type natriuretic peptide: a cross‐sectional study

Abstract: AimsLeft ventricular hypertrophy, obesity, hypertension, and N‐terminal B‐type natriuretic peptide (Nt‐proBNP) predict left ventricular diastolic dysfunction with preserved systolic function (DD‐PSF). Self‐rated health (SRH) is shown to be associated with chronic diseases, but the association of SRH with DD‐PSF is unclear. In light of the clinical implications of DD‐PSF, the following goals are of considerable importance: (1) to determine the role of SRH in patients with DD‐PSF in the general population and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Additionally, women may perceive impairment as more severe compared to men [ 134 ]. Two community studies showed that a lower quality of life or lower self-rated health, respectively, are associated with asymptomatic LVDD [ 5 , 136 ], and counter-intuitively, the age-adjusted association of self-rated health with LVDD was only significant in men (OR = 3.49 (95% CI: 1.0, 11.9)) [ 136 ].…”
Section: Mainmentioning
confidence: 99%
“…Additionally, women may perceive impairment as more severe compared to men [ 134 ]. Two community studies showed that a lower quality of life or lower self-rated health, respectively, are associated with asymptomatic LVDD [ 5 , 136 ], and counter-intuitively, the age-adjusted association of self-rated health with LVDD was only significant in men (OR = 3.49 (95% CI: 1.0, 11.9)) [ 136 ].…”
Section: Mainmentioning
confidence: 99%